(untitled) - Herman, Stephen L. (Clifton Park, NY, 2005)
Success in the electronics field requires a substantial background in mathematics. This updated book is written to provide beginning students with these needed skills. Practical, easy-to-understand problems help prepare students for the types of problems that professional electronic technicians face everyday. As part of the successful Practical Problems in Mathematics series, this fourth edition features expanded coverage of scientific notation, increased problems to be solved using a calculator, additional information on RLC circuits, and a new unit on simultaneous equations that includes coverage of Kirchoff’s Law.
Keywords: Electric engineering,Kỹ thuật điện; Mathematics,Toán học